2015
DOI: 10.1007/s11242-015-0537-2
|View full text |Cite
|
Sign up to set email alerts
|

Conjugate Heat Transfer in an Annulus with Porous Medium Fixed Between Solids

Abstract: Conjugate heat transfer is an important area of research which has been in demand due to its applications related to various scientific and engineering fields. The current research is focused to study the heat transfer in a porous medium sandwiched between two solid walls of an annular vertical cylinder. The prime focus of the current study was to evaluate the effect of solid wall thickness, the influence of variable wall thickness at inner and the outer radius, the conductivity ratio and the solid wall conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 104 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…Reddy and Narasimham 50 performed numerical simulations to study combined conduction-convection in an enclosed annular region between inner heated rod and an outer cylinder for vast ranges of thermal conductivity ratios and presented thermal transfer correlations. Later, conjugate buoyant transport in a porous material placed in the annular region between two solid cylinders was numerically analyzed by Badruddin et al 51 Recently, John et al 52 made a detailed review on conjugate thermal transfer analysis covering various applied and theoretical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Reddy and Narasimham 50 performed numerical simulations to study combined conduction-convection in an enclosed annular region between inner heated rod and an outer cylinder for vast ranges of thermal conductivity ratios and presented thermal transfer correlations. Later, conjugate buoyant transport in a porous material placed in the annular region between two solid cylinders was numerically analyzed by Badruddin et al 51 Recently, John et al 52 made a detailed review on conjugate thermal transfer analysis covering various applied and theoretical aspects.…”
Section: Introductionmentioning
confidence: 99%
“…Badruddin et al. 19 studied the effect of solid walls thickness, conductivity and conductivity ratio on convection flow in porous media embedded between two solid walls. Taherzadeha and Saidi 20 have discussed the effect of generating heat on convective flow within saturated porous medium embedded in an annulus enclosure.…”
Section: Introductionmentioning
confidence: 99%
“…Al-Farhany et al [31], have shown in their work that the Darcy number is inversely related with average Nusselt number. Badruddin et al [32] analyzed the role of varying conductivity ratio as well as the relative thickness of two solid surfaces in an annulus. They reported that the conductivity ratio as well as the relative thickness of participating solids have impacts on heat transfer characteristics.…”
Section: Introductionmentioning
confidence: 99%